The role of the social network in the study of adherence to diabetic retinopathy screening programs - Pereira, A. P.; Afonso, A.; Laureano, R. M. S.; Neto, F. B. de L. (Scientific Reports, 2024)
Diabetic retinopathy screenings are a vital strategy to avoid the severe consequences of this disease. However, their success depends on the adherence of the target population. The present work aims to review the adherence to diabetic retinopathy screening, more specifically the influence of the persons with diabetes’ social network (contacts between persons with diabetes) on their screening behaviour. The used data set comprises information of 75,921 persons with diabetes, distributed by 20 Primary Health Centre Groups of the Portuguese North Region. Persons with diabetes of the same Group were organized in an N-by-N matrix, resulting in 20 social networks. Network metrics were calculated and its relationship with the adherence to screening was analysed using two perspectives: correlation between global network metrics and adherence rate; cluster analyses based on node level metrics. The results obtained show that: (1) Less connected networks, strongly divided into communities and with a great number of connected components, present the highest adherence rates. (2) The node level metrics allow the identification of groups where the problem of non-adherence is especially high. (3) The non-adherence phenomenon is especially evident in a small group of highly connected individuals. We believe that these results are of utmost relevance as a starting point for future research and as support to the planning of interventions related to diabetic retinopathy screening adherence.